Pulsations in the Earth's Lower Ionosphere Synchronized With Solar Flare Emission. Issue 10 (17th October 2017) - Hayes, Laura A.; Gallagher, Peter T.; McCauley, Joseph; Dennis, Brian R.; Ireland, Jack; Inglis, Andrew
Abstract: Solar flare emission at X‐ray and extreme ultraviolet (EUV) energies can cause substantial enhancements in the electron density in the Earth's lower ionosphere. It has now become clear that flares exhibit quasi‐periodic pulsations with timescales of minutes at X‐ray energies, but to date, it has not been known if the ionosphere is sensitive to this variability. Here using a combination of very low frequency (24 kHz) measurement together with space‐based X‐ray and EUV observations, we report pulsations of the ionospheric D region, which are synchronized with a set of pulsating flare loops. Modeling of the ionosphere show that the D region electron density varies by up to an order of magnitude over the timescale of the pulsations (∼ 20 min). Our results reveal that the Earth's ionosphere is more sensitive to small‐scale changes in solar soft X‐ray flux than previously thought and implies that planetary ionospheres are closely coupled to small‐scale changes in solar/stellar activity. Key Points: Pulsations detected in ionospheric D region are synchronized with flare X‐ray pulsations D region electron density varies by up to an order of magnitude over 20 min during the pulsations Effective ionospheric recombination coefficient can be calculated as a function of varying X‐ray flux